L‐glutamine protects mouse brain from ischemic injury via up‐regulating heat shock protein 70. (20th June 2019) - Luo, Long‐Long; Li, Yong‐Fang; Shan, Hui‐Min; Wang, Li‐Ping; Yuan, Fang; Ma, Yuan‐Yuan; Li, Wan‐Lu; He, Ting‐Ting; Wang, Yu‐Yang; Qu, Mei‐Jie; Liang, Huai‐Bin; Zhang, Zhi‐Jun; et al.
Abstract: Introduction: L‐glutamine is an antioxidant that plays a role in a variety of biochemical processes. Given that oxidative stress is a key component of stroke pathology, the potential of L‐glutamine in the treatment of ischemic stroke is worth exploring. Aims: In this study, we investigated the effect and mechanisms of action of L‐glutamine after cerebral ischemic injury. Results: L‐glutamine reduced brain infarct volume and promoted neurobehavioral recovery in mice. L‐glutamine administration increased the expression of heat‐shock protein 70 (HSP70) in astrocytes and endothelial cells. Such effects were abolished by the coadministration of Apoptozole, an inhibitor of the ATPase activity of HSP70. L‐glutamine also reduced oxidative stress and neuronal apoptosis, and increased the level of superoxide dismutase, glutathione, and brain‐derived neurotrophic factor. Cotreatment with Apoptozole abolished these effects. Cell culture study further revealed that the conditioned medium from astrocytes cultured with L‐glutamine reduced the apoptosis of neurons after oxygen‐glucose deprivation. Conclusion: L‐glutamine attenuated ischemic brain injury and promoted functional recovery via HSP70, suggesting its potential in ischemic stroke therapy.